STUDY OF SCIENCE LITERACY ABILITY OF CHEMISTRY PRE-SERVICE TEACHERS IN HYDROPONICS PRACTICUM - Bahriah, Evi Sapinatul; Siti Suryaningsih; Ivan Muhammad Maful (Universitas Negeri Surabaya, 2024)
The ability of scientific literacy of indonesian student categorized as low. One of the factor that contribute is that the ability of a scientific literacy of a teacher. The hydroponics practical in a biotechnology’s subject, can be measure the ability of scientific literacy of a student because there is a science process in it. The aim of this reasearch is to determine the ability of scientific literacy of chemisty pre-service Teachers for the knowledge and competency’s aspects in a hydroponics topic. The method that used in this reasearch was quantitative descriptive analysis and the technique of data collection by spreading the instrument in a purposive sampling technique to 50 chemisty pre-service teachers. The instrment that used was 10 items of essay questions. The data was analyse with a scoring method and then will change it into a percentage. Based on the reasearch, the ability of scientific literacy of a student for knowledge’s aspect is 68.5% and for the competency is 62.2%. From that data, it can conclude that the ability of scientific literacy of chemistry chemisty pre-service teachers for knowledge and comptency aspects categorized good.